Association of Blood and Seminal Plasma Cadmium and Lead Levels With Semen Quality in Non-Occupationally Exposed Infertile Men in Abakaliki, South East Nigeria - Ademola C Famurewa; Emmanuel I Ugwuja (Tehran University of Medical Sciences, 2017)
Objective: To evaluate association of blood and seminal plasma lead and cadmium with sperm quality of non-occupationally exposed male partners of couples with infertility. Materials and methods: A cross-sectional study was conducted on 75 men aged 20-45 years (mean = 37.1 ± 7.0 yrs.) with infertility recruited from the Fertility Clinic of a hospital in Abakaliki. Sperm count done in accordance with the WHO guidelines was used to classify the participants as normospamia, oligospermia and azospermia. Atomic absorption spectrophotometer was used to determine lead and cadmium levels in plasma from blood and semen. Results: There were 15 azospermics, 22 oligospermics and 36 normospermics. Seminal and blood plasma cadmium as well as blood plasma lead were significantly (p < 0.01) higher in azospermic and oligospermic men compared to normospermic men. However, while seminal plasma lead was significantly (p < 0.05) higher in oligospermic and normospernic men than in azospermic men, the seminal plasma lead was comparable between oligospermic and normospermic men. Significant inverse associations (p < 0.01) were found between blood and seminal cadmium levels and sperm count, motility and morphology; blood lead was inversely correlated with sperm count only. Conclusion: The study suggests that environmental exposure to cadmium and lead may contribute to development of poor sperm quality and infertility in men of reproductive age in Nigeria.